Safety evaluation of the food enzyme pullulanase from genetically modified Bacillus subtilis strain NZYM‐AK. (18th August 2017) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Cravedi, Jean‐Pierre; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; Mennes, Wim; et al.
Abstract: The food enzyme considered in this opinion is a pullulanase (pullulan 6‐α‐glucanohydrolase; EC 3.2.1.41), produced with the genetically modified Bacillus subtilis strain NZYM‐AK by Novozymes A/S (Denmark). The pullulanase food enzyme is intended to be used in starch processing for the production of glucose syrups. Since the residual amounts of total organic solids (TOS) in glucose syrups after filtration and purification during starch processing were considered negligible, no dietary exposure was calculated. Genotoxicity tests made with the food enzyme indicated no genotoxic concern. A repeated dose 90‐day oral toxicity study in rodents, carried out with a pullulanase produced with a predecessor strain, showed no concern with respect to systemic toxicity. The allergenicity was evaluated by searching for similarity of the amino acid sequence to those of known allergens; no match was found. The Panel considers that there are no indications for allergic reactions. Based on the microbial source, genetic modifications performed, the manufacturing process, the compositional and biochemical data provided, the findings in the toxicological studies and allergenicity assessment, the Panel concludes that this food enzyme does not give rise to safety concerns under the intended conditions of use.